AN ALTERNATIVE AND SIMPLE MANNER TO CALCULATE THE THERMAL EFFICIENCY OF COMBUSTION ENGINES - Rocha, F. N. C.; Martins, J. A.; Romão, E. C. (Revista de Engenharia Térmica, 2014)
This papers aims to present techniques and methods to develop an alternative equation to determine the thermal efficiency of internal combustion engines. Towards interpolation of data, obtained from thermodynamic tables, it presents a function that allows a faster calculation of efficiency for combustion engines.